Utilization of Silica Nanoparticles from Rice Husks for Improving the Mechanical Properties of Dental Materials: A Literature Review - Sopan Sinamo; Slamat Tarigan; Saharman Gea; Deddi Prima Putra (HM Publisher, 2022)
Rice husk is a waste product whose utilization is not optimal in Indonesia. Rice husks contain organic materials in the form of cellulose, hemicellulose, and lignin; and minerals in the form of silica, alkali, and trace elements. The silica content in rice husks is very high, ranging from 87-97% to other minerals. Silica nanoparticles from rice husks were synthesized through various methods, including the sol-gel method, the combustion method, and the combination method, to obtain the purity and size of the silica particles up to the manometer scale. Mixing silica nanoparticles from rice husk to dental material at a certain concentration is effective in producing better mechanical properties. Silica nanoparticles synthesized from rice husks have the potential as fillers and reinforcements that can improve the mechanical properties of dental materials. Besides that, the price is more economical because the raw materials come from Indonesian natural waste. This literature review aims to describe the method of synthesizing silica nanoparticles from rice husks and their effectiveness in improving the mechanical properties of dental materials.